Requirements elicitation applied to electronic voting system - Thomas, Pablo Javier (2005)
Nowadays, technology has become the key element to carry out the management, organization and fulfillment of the electoral process. The electoral process should be understood as the actions that entail the making of the electoral roll, citizen identification, the act of voting, the counting of votes and the reporting of the results. The act of voting is considered as the software system to be specified, using as the source of information the National Electoral Code of Argentina Republic. The scenario technique is applied in order to obtain the system requirements, with the purpose of reducing the semantic gap between the legal written documentation and the implementation of an electronic voting system. Constraints regarding the compliance with the current legislation, the specific vocabulary, and the need to have, at least, one stakeholder that interprets the Law are analyzed. An elicitation technique, which emphasized the role of Language of the Universe of Discourse, is proposed. Finally, it is stressed the importance of having a requirements specification with the necessary steps for the casting of the vote, including all the alternative situations, from which a software design can be done.